Bioresponsive nanoplatforms for imaging and therapy of cardiovascular diseases. Issue 1 (31st January 2022) - Li, Chenwen; Wu, Peng; Dou, Yin; Li, Qi; Zhang, Jianxiang
Abstract: Cardiovascular diseases (CVDs) are still the first cause of death worldwide. Conventional small molecular diagnostic and therapeutic agents generally show limited in vivo detection sensitivity and efficacies, due to their non‐targeting distribution and/or low accumulation at diseased sites. New strategies are required to better address the unmet need for the management of CVDs. Bioresponsive nanoplatforms with excellent triggerable release profiles and desirable targeting capability have demonstrated intriguing prospects in detection, prevention, and therapy of CVDs. This review summarizes recent advances in bioresponsive nanoplatforms responsive to biochemical stimuli, such as pH, redox potential, reactive oxygen species, enzymes, and adenosine triphosphate. We highlight the applications of different bioresponsive nanoplatforms for imaging and therapy of typical CVDs, including myocardial infarction, atherosclerosis, thrombosis, ischemic stroke, and heart failure. Finally, existing challenges and future perspectives are also discussed, with respect to the development and translation of bioresponsive nanoplatforms for CVDs. Abstract : Cardiovascular diseases (CVDs) are still the first cause of global death. This review summarizes the applications of different bioresponsive nanoplatforms for imaging and therapy of typical CVDs, including myocardial infarction, atherosclerosis, thrombosis, ischemic stroke, and heart failure. Existing challenges and future perspectives are also discussed.